Spotlight on Digital Eye Strain - Mylona I; Glynatsis MN; Floros GD; Kandarakis S (Clinical Optometry, 2023)
Ioanna Mylona,1 Mikes N Glynatsis,2 Georgios D Floros,3 Stylianos Kandarakis4 1Department of Ophthalmology, General Hospital of Katerini, Katerini, Greece; 2Department of Ophthalmology, ‘Hippokration’, General Hospital of Thessaloniki, Thessaloniki, Greece; 3 2nd Department of Psychiatry, Aristotle University of Thessaloniki, Thessaloniki, Greece; 4 1st Department of Ophthalmology, General Hospital “G. Gennimatas”, National and Kapodistrian University of Athens, Athens, GreeceCorrespondence: Ioanna Mylona, Ophthalmology Department, General Hospital of Serres, Serres, 62210, Greece, Tel +306941406978, Email milona_ioanna@windowslive.comAbstract: Digital Eye Strain (DES) is a clinical syndrome manifested with visual disturbances and/or ophthalmic dysfunction related to the usage of screen-enabled digital equipment. This term is gradually replacing the older term computer vision syndrome (CVS) that focused on the same symptoms found on personal computer users. DES is encountered more frequently during the past years due to the explosive increase in the usage of digital devices and subsequent increase in time in front of any screens. It presents with a series of atypical symptoms and signs stemming from asthenopia, dry eye syndrome, preexisting untreated vision issues and poor screen ergonomics. This review summarizes research data to date to determine whether the concept of DES has been conclusively defined and demarcated as a separate entity and if sufficient guidance is offered on professionals and the lay public. The maturity of the field, grouping of symptoms, examination techniques, treatment and prevention modalities are summarily presented.Keywords: digital eye strain, computer vision syndrome, classification, management